Towards multi-field D-brane inflation in a warped throat - Chen, Heng-Yu; Gong, Jinn-Ouk; Koyama, Kazuya; Tasinato, Gianmassimo (Journal of cosmology and astroparticle physics, 2010)
We study the inflationary dynamics in a model of slow-roll inflation in warped throat. Inflation is realized by the motion of a D-brane along the radial direction of the throat, and at later stages instabilities develop in the angular directions. We closely investigate both the single field potential relevant for the slow-roll phase, and the full multi-field one including the angular modes which becomes important at later stages. We study the main features of the instability process, discussing its possible consequences and identifying the vacua towards which the angular modes are driven.